Pentingnya Safety Riding Dalam Keselamatan Relawan Escorting Ambulans - Ahmad, Rifqi Fauzi; Tjahjodiningrat, Harry; Warsana, Dedi (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2023)
Medical treatment for the community needs to be carried out quickly and immediately. For this reason, safety riding is knowledge that needs to be understood by volunteers accompanying ambulances in ensuring quick medical treatment to their destination and safety for these volunteers in accompanying ambulances in carrying out their duties. This research aims to determine the importance of understanding ambulance escort volunteers regarding safety riding in accompanying ambulances in carrying out their duties. The method in this research was carried out using a descriptive qualitative method using a qualitative ethnographic approach. Data was collected through an interview process with the ambulance escorting volunteer community in Greater Bandung. The research results show that awareness of the importance of driving safety among ambulance escorting volunteers is very high. Factors such as defensive driving skills, use of protective equipment, and compliance with traffic laws have a direct impact on the success of an emergency medical mission. Ambulance escort volunteers' practice and understanding of safe driving methods tends to respond to emergency situations more effectively and safely. Keywords: Safety Riding, medical, Voulenteers, Escorting Ambulance